2015
DOI: 10.1007/s10735-015-9638-z
|View full text |Cite
|
Sign up to set email alerts
|

Sox4 enhances chondrogenic differentiation and proliferation of human synovium-derived stem cell via activation of long noncoding RNA DANCR

Abstract: Mesenchymal stem cells (MSCs) have several features that make them an attractive option for potentiating cartilage repair. Synovium-derived (SMSCs) have been recently recognized as an excellent source. SRY-related HMG-box (Sox) family plays an important role in the proliferation and differentiation of SMSCs. However, the role of Sox4 in human SMSCs remains elusive. In the present study, we investigated the role of Sox4 in SMSCs through gain-of-function studies and found that Sox4 promoted cell proliferation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…SMSCs have shown promising efficiency for cell-based regeneration of damaged articular cartilage [14]. Our previous data demonstrated that chondrogenic differentiation of SMSCs was promoted by lncRNA DANCR [12,13]. In the present study, we characterized the underlying molecular mechanism that overexpression of DANCR down-regulates miR-1305 .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…SMSCs have shown promising efficiency for cell-based regeneration of damaged articular cartilage [14]. Our previous data demonstrated that chondrogenic differentiation of SMSCs was promoted by lncRNA DANCR [12,13]. In the present study, we characterized the underlying molecular mechanism that overexpression of DANCR down-regulates miR-1305 .…”
Section: Discussionmentioning
confidence: 77%
“…Informed consents were obtained from the patients. The protocol for SMSCs isolation was established as previously described [13]. Briefly, synovial tissue was collected from the patients with osteoarthritis during the operations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent study identified that the transcription factor, SOX4, can regulate the proliferation and chondrogenic differentiation of human synovium-derived MSCs (SMSCs) and that activation of the IncRNA, DANCR , is involved in this process (90). Here, SMSCs were extracted from the synovium of osteoarthritis (OA) patients and aggregate cultures were utilized for in vitro chondrogenesis.…”
Section: Incrnas Regulating Chondrocyte Differentiationmentioning
confidence: 99%
“…With further analyses to find biological function of lncRNAs and their involvement in the mechanism of differentiation, it has been determined that two ZBED3-AS1 and CTA-941F9.9 lncRNAs are most likely playing important roles in chondrogenic differentiation process (4). Several other reports focused on the findings about the regulatory roles of lncRNAs in self-renewal and differentiation into any lineage, and explained the underlying molecular mechanisms (5,6 (8). Moreover, lncRNA H19 promotes osteoblast differentiation of hMSCs Via TGF-β1/Smad3/HDAC signaling pathway by deriving miR-675 and may serve as a potential target for enhancing bone formation in vivo (9).…”
mentioning
confidence: 99%